2011
DOI: 10.1590/s0004-28032011000300011
|View full text |Cite
|
Sign up to set email alerts
|

Protection of estrogen in portal hypertension gastropathy: an experimental model

Abstract: -Context -Portal hypertension is a complication secondary to cirrhosis that is characterized by increased blood flow and/or vascular resistance in the portal system, causing the appearance of a hyperdynamic collateral circulation. Partial portal vein ligation is an experimental model used in rats to study the pathophysiological mechanisms involved in pre-hepatic portal hypertension. Estrogen E2 is an antioxidant molecule with various physiological actions. Objectives -To evaluate the antioxidant activity of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Moreover, it can provide measurements in the portal circulation [29] that cannot be performed accurately in humans because of ethical and technical limitations [30]. In the current study, portal pressure in the PPVL group was significantly increased in comparison with the control group.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Moreover, it can provide measurements in the portal circulation [29] that cannot be performed accurately in humans because of ethical and technical limitations [30]. In the current study, portal pressure in the PPVL group was significantly increased in comparison with the control group.…”
Section: Discussionmentioning
confidence: 57%
“…PPVL is an experimental model used in rats to study the histopathological mechanisms involved in prehepatic PHT with a maintained liver integrity and a hyperdynamic circulation that develops in a short and predicted period 1 week after induction [29]. Moreover, it can provide measurements in the portal circulation [29] that cannot be performed accurately in humans because of ethical and technical limitations [30].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that E 2 reduced portal pressure and increased hepatic blood flow in castrated and cirrhotic model rats, but the effect was significantly inhibited by ICI-182780 [62,81]. E 2 played a protective role by acting as an antioxidant, because the hemodynamic changes involved in PHT led to increased ROS, which triggered oxidative stress [82].…”
Section: Role Of Estrogens In the Improvement Of Portal Hypertension mentioning
confidence: 99%
“…E 2 played a protective role by acting as an antioxidant, because the hemodynamic changes involved in PHT led to increased ROS, which triggered oxidative stress [82]. In castrated rats, a significant increase in the activity of antioxidant enzymes and lipid peroxidase was observed, which might occur to compensate for the absence of circulating E 2 , promoted by castration, but even then it was not effective in reducing lipid peroxidase [81,83,84]. Estrogen replacement could reverse this effect, reverting to the values of the control animals [84].…”
Section: Role Of Estrogens In the Improvement Of Portal Hypertension mentioning
confidence: 99%
“…In the portal hypertension dilation of the splanchnic veins occurs, and collateral circulation is developed. This situation may happen with diseases in pre, intra or post-hepatics stages 10 . Thrombosis of the portal vein or splenic vein triggers pre-hepatic portal hypertension.…”
Section: Introductionmentioning
confidence: 99%